ANALISIS RENCANA LIFE CYCLE COST PADA GEDUNG MALL PELAYANAN PUBLIK KABUPATEN SIKKA - Yanuarius Da Iry; Triapriono Kaidu (Program Studi Teknik Sipil, 2025)
Life Cycle Cost (LCC) is the cost required by a building during its planned life. Included in this cost are the planning and construction costs called initial costs, costs incurred during the operation or use of the construction called operational costs, routine maintenance and repair costs called maintenance costs, as well as the cost of demolition and recycling of unused materials. This is done when the building can no longer function. The purpose of this study is to find out how to design the Life Cycle Cost (LCC) method. Initial costs, operating costs, maintenance costs, and demolition costs. In this case, the building reviewed is the public service mall (MPP) building in Sikka Regency during the planned life of 25 years. Through the calculation process, it can be detailed as follows: Initial costs of Rp. 3,544,566,370.89 (39%), operational costs of Rp. 1,744,200,000 (19%), maintenance costs of Rp. 3,431,339,671 (38%) and demolition costs of Rp. 354,456,600.00 (4%)